The Effectiveness of Da’i as Zakat Executors in Strengthening Zakat Collection: Evidence from BAZNAS Dharmasraya Regency - Aswen, Latif; Karni, Awis; Zainal; Nofrianti, Mami; Yustiloviani (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2025)
This study examines the transformation of the role of da’i within BAZNAS of Dharmasraya Regency, where their function has expanded beyond the delivery of religious messages to encompass strategic responsibilities in the collection and management of zakat. The research seeks to analyze how this functional transformation occurs and to assess its effectiveness in increasing the potential collection of zakat, infak, and sadaqah (ZIS). Employing a qualitative methodology with a transformative approach, this study adopts the Community-Based Research (CBR) model, which emphasizes active collaboration among researchers, da’i, and local communities in identifying challenges and formulating context-sensitive solutions. Data were generated through participatory engagement, enabling an in-depth understanding of the social and institutional dynamics surrounding zakat management. The findings indicate that the repositioning of da’i as zakat executors has significantly enhanced collective community awareness of the religious and social importance of zakat, while also strengthening zakat management systems grounded in local culture and community potential. Furthermore, the integration of cultural approaches and managerial capacity-building initiatives has proven effective in reinforcing the role of da’i as agents of social change, particularly in promoting community empowerment and sustainable zakat governance.